Process for improving wear resistance of laser cladding titanium alloy coating by taking nitrogen as protective gas

By using nitrogen as protective gas on the titanium alloy for laser cladding, the titanium alloy cladding layer is formed, which solves the problem of poor wear resistance of titanium alloy and achieves a significant improvement in hardness and wear resistance.

CN119710686AActive Publication Date: 2025-03-28天津滨海雷克斯激光科技发展有限公司
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510227789.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-03-28
Estimated Expiration
2045-02-28

AI Technical Summary

Technical Problem

The poor wear resistance of titanium alloys limits their use in certain applications.

Method used

Nitrogen is used as the protective gas, and laser cladding is carried out through control materials and process technology to form a titanium alloy cladding layer without hard particles.

Benefits of technology

The hardness and wear resistance of the titanium alloy cladding layer are significantly improved, exceeding the performance when using argon as a protective gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710686A_ABST
    Figure CN119710686A_ABST
Patent Text Reader

Abstract

According to the process for improving the wear resistance of the laser cladding titanium alloy coating by taking nitrogen as shielding gas, titanium alloy powder or titanium alloy composite alloy powder which does not contain any hard particles is used as a laser cladding alloy raw material, laser cladding equipment, laser parameters and process parameters of powder feeding gas are regulated and controlled, the nitrogen is used as the shielding gas, and the wear resistance of the laser cladding titanium alloy coating is improved. Laser cladding is carried out on an ALPHA titanium alloy base body, an NEAR-ALPHA titanium alloy base body and an ALPHA-BETA titanium alloy base body which do not contain Sn, Pd and Ru, and a laser cladding titanium alloy cladding layer is obtained. The raw material powder of the laser cladding alloy is titanium alloy powder without hard particles or hard phases, laser cladding is carried out by controlling materials and a process technology and taking nitrogen as shielding gas, and a titanium alloy cladding layer is obtained on the surface of a titanium alloy matrix; and the hardness and the wear resistance are obviously higher than those of a titanium alloy cladding layer which is subjected to laser cladding by taking argon as shielding gas in the same material process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of laser cladding, and in particular to a process for improving the wear resistance of laser cladding titanium alloy coating by using nitrogen as protective gas. Background Art

[0002] Among the metal materials used in industrial applications, titanium alloys have the advantages of lower density, higher specific strength, and better corrosion resistance. They are widely valued and used in aerospace, defense industry, automobiles, medical treatment, marine engineering and other fields. However, titanium alloys have poor wear resistance, which limits their application in some fields.

[0003] In order to improve the wear resistance of titanium alloy workpieces, using argon as a protective gas and laser cladding technology to clad a composite alloy wear-resistant layer on the worn surface of the workpiece is currently one of the main methods to increase the service life of worn workpieces.

[0004] In order to improve the wear resistance of titanium alloy workpieces, many studies have focused on using high-hardness particles such as tungsten carbide, titanium carbide or boron carbide to evenly mix with metal alloy powder as laser cladding materials, and laser cladding under argon protection to obtain metal-based composite materials composed of high-hardness particles and alloy matrix as laser cladding wear-resistant layers, such as: WC+NiCrBSi alloy, WC+Inconel625 alloy, SiC+NiCrBSi alloy, TiC+NICrBSi alloy, etc. Most of these are laser cladding metal-based composite cladding layers using hard particles (including carbides or hard ceramic particles) as reinforcement phases. This type of laser cladding composite metal material wear-resistant coating requires that the carbide or hard ceramic hard particles have good compatibility with the base metal of the cladding layer in order to better combine and ensure that the hard particles will not peel off during wear, especially abrasive wear, which limits its application to a certain extent. Summary of the invention

[0005] The present invention aims to solve the deficiencies of the prior art and provides a process for improving the wear resistance of laser cladding titanium alloy coatings by using nitrogen as a protective gas. The process is characterized in that no hard particles are added to the laser cladding alloy, and by controlling the material process technology, nitrogen is used as a protective gas instead of the conventionally used argon as a protective gas. Titanium alloy powder is used as a cladding material for laser cladding. The hardness and wear resistance of the cladding layer are significantly higher than those of the laser cladding titanium alloy coating using argon as a protective gas in the same cladding material process.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A process for improving the wear resistance of laser cladding titanium alloy coating by using nitrogen as a protective gas, using titanium alloy powder or titanium alloy composite alloy powder without any hard particles as laser cladding alloy raw materials, and adjusting the laser cladding equipment, laser parameters, and process parameters of powder feeding gas. Using nitrogen as a protective gas, laser cladding is performed on ALPHA titanium alloy, NEAR-ALPHA titanium alloy, and ALPHA-BETA titanium alloy substrates that do not contain Sn, Pd, or Ru to obtain a laser cladding titanium alloy cladding layer.

[0008] The first type of laser cladding alloy raw materials are titanium alloy powders with a Ti content of not less than 80 wet.%, specifically:

[0009] A spherical titanium alloy powder containing alloy elements Al: 3.0wt.%-7.0wt.%, V: 3.0wt.%-5.0wt.%, Mo: ≤5.0wt.%, Zr ≤5.0wt.%, the total amount of other elements less than 0.5wt.%, the content of impurity element S less than 0.01 wt.%, and Ti content not less than 80wt.%; the particle size of the spherical titanium alloy powder is in the range of 45μm-150μm and conforms to the spherical alloy powder of normal distribution.

[0010] The second type of laser cladding alloy raw materials are titanium alloy composite alloy powders composed of spherical titanium alloy powders with a Ti content of not less than 85wet.% and single-element Mo powder, specifically:

[0011] A titanium alloy composite alloy powder containing alloy elements Al: 3.0wt.%-7.0wt.%, V: 2.0wt.%-5.0wt.%, the total amount of other elements less than 0.5wt.%, the content of impurity element S less than 0.01wt.%, the content of Ti not less than 85wt.%, and a spherical titanium alloy powder with a particle size in the range of 45μm-150μm that conforms to normal distribution and a pure Mo powder uniformly mixed;

[0012] The amount of pure Mo powder added is in the range of 3wt.%-6wt.%; the particle size of the pure Mo powder is 10μm-55μm; and the molybdenum content of the pure Mo powder is not less than 99wt%.

[0013] The above-mentioned process of using nitrogen as a protective gas to improve the wear resistance of the laser cladding titanium alloy coating has the following specific steps:

[0014] S1. Preparation of raw materials for laser cladding alloy:

[0015] Prepare laser cladding alloy raw materials according to the set requirements. For composite titanium alloy powder and composite alloy powder, the powders need to be mixed according to the set ratio and mixed evenly with a powder mixer. The laser cladding alloy raw materials should be dried before use;

[0016] S2. Clean the surface of the workpiece where laser cladding is required:

[0017] Degreasing and removing surface pollutants, the surface roughness of the substrate to be clad should be lower than Ra12.6. When the room temperature is lower than 15°C, the substrate needs to be preheated before cladding, and the preheating temperature is 150°C;

[0018] S3, Laser Cladding:

[0019] Adjust relevant parameters before cladding: adjust the distance between the laser head nozzle and the surface to be clad, and adjust the size and uniformity of the laser spot on the workpiece surface;

[0020] Set the powder feeding rate;

[0021] Set the powder feeding gas pressure-flow;

[0022] Set the shielding gas pressure-flow;

[0023] Set the laser scanning speed;

[0024] Set the laser power according to the required laser energy density;

[0025] Set the overlap width between laser cladding passes;

[0026] Operate the controller-robot for laser cladding;

[0027] S4. Post-processing of laser cladding:

[0028] The surface of the laser cladding layer is ground as required.

[0029] Laser cladding is performed using a multi-mode continuous wave fiber laser with a power of not less than 4kW and a coaxial powder feeding laser head.

[0030] A rotary quantitative pneumatic powder feeder is used to transport the laser cladding alloy raw materials, and argon with a purity higher than 99.9% is used as the powder feeding gas.

[0031] The nitrogen used as the protective gas is high-purity nitrogen with a nitrogen content higher than 99.99% and an oxygen content lower than 0.01%.

[0032] The beneficial effects of the present invention are as follows: in the present invention, the alloy raw material powder for laser cladding is a titanium alloy powder without hard particles or hard phases. By controlling materials and process technology, nitrogen is used as a protective gas instead of argon gas conventionally used as a protective gas to perform laser cladding, and a titanium alloy cladding layer is obtained on the surface of the titanium alloy substrate. The hardness and wear resistance of the titanium alloy cladding layer are significantly higher than those of the titanium alloy cladding layer obtained by laser cladding using argon gas as a protective gas using the same material and process. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Attached Figure 1The photographs are of the titanium alloy laser cladding sample TA using argon as the protective gas and the titanium alloy laser cladding sample TN using nitrogen as the protective gas in the specific embodiment 1 of the present invention;

[0034] Attached Figure 2 The morphology photographs of the worn samples of samples TA and TN in specific embodiment 1 of the present invention after the wet sand-rubber wheel abrasive wear test according to ASTM G105 standard;

[0035] Attached Figure 3 This is a metallographic photograph of the cross section of the laser cladding layer of the titanium alloy laser cladding sample TA observed under an optical metallographic microscope at a magnification of 200 times in specific embodiment 1 of the present invention with argon as the protective gas;

[0036] Attached Figure 4 This is a microhardness test photograph of a titanium alloy laser cladding sample TA using argon as a protective gas in specific embodiment 1 of the present invention;

[0037] Attached Figure 5 This is a metallographic photograph of the cross section of the laser cladding layer of the titanium alloy laser cladding sample TN using nitrogen as the protective gas in the specific embodiment 1 of the present invention observed under an optical metallographic microscope at a magnification of 200 times;

[0038] Attached Figure 6 This is a microhardness test photograph of a titanium alloy laser cladding sample TN using nitrogen as a protective gas in specific embodiment 1 of the present invention;

[0039] Attached Figure 7 The morphology photographs of the worn samples of samples TMA and TMN in specific embodiment 2 of the present invention after the wet sand-rubber wheel abrasive wear test according to ASTM G105 standard;

[0040] Attached Figure 8 This is a metallographic photograph of the cross section of the laser cladding layer of the titanium alloy composite alloy powder laser cladding sample TMA using argon as the protective gas in specific embodiment 2 of the present invention observed under an optical metallographic microscope magnified 200 times;

[0041] Attached Fig. 9 This is a microhardness test photograph of a sample TMA of a titanium alloy composite alloy powder laser cladding using argon as a protective gas in specific embodiment 2 of the present invention;

[0042] Attached Fig.10 This is a metallographic photograph of the cross section of the laser cladding layer of the titanium alloy composite alloy powder laser cladding sample TMN using nitrogen as the protective gas in specific embodiment 2 of the present invention observed under an optical metallographic microscope magnified 200 times;

[0043] Attached Fig.11This is a microhardness test photograph of a sample TMN of titanium alloy composite alloy powder laser cladding using nitrogen as a protective gas in specific embodiment 2 of the present invention;

[0044] Attached Fig.12 The titanium alloy composite alloy powder laser cladding sample TMN using nitrogen as the protective gas in the specific embodiment 2 of the present invention is attached Fig.11 Microhardness test photos of points;

[0045] Attached Fig.13 This is a micro-area SEM-EDS analysis photograph of the dendrite structure of the laser cladding layer of the titanium alloy composite alloy powder laser cladding sample TMN using nitrogen as the protective gas in the specific embodiment 2 of the present invention;

[0046] The following is a detailed description of the embodiments of the present invention with reference to the accompanying drawings. DETAILED DESCRIPTION

[0047] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The embodiments are only used to explain the present invention and are not used to limit the scope of the present invention. The present invention is described in more detail by way of example with reference to the accompanying drawings in the following paragraphs. The advantages and features of the present invention will become clearer according to the following description. It should be noted that the accompanying drawings are all in a very simplified form and are not in precise proportions, and are only used to facilitate and clearly assist in explaining the purpose of the embodiments of the present invention.

[0048] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0049] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:

[0050] In this process, nitrogen is used as a protective gas to improve the wear resistance of laser cladding titanium alloy coatings. Titanium alloy powder or titanium alloy composite alloy powder that does not contain any hard particles is used as the laser cladding alloy raw material. By adjusting the laser cladding equipment, laser parameters, and process parameters of the powder feeding gas, nitrogen is used as a protective gas to perform laser cladding on ALPHA (α) titanium alloy, NEAR-ALPHA (near-α) titanium alloy, and ALPHA-BETA (α-β) titanium alloy substrates that do not contain Sn, Pd, or Ru, and a laser cladding titanium alloy cladding layer with a hardness higher than 54HRC is obtained.

[0051] The first type of laser cladding alloy raw materials are titanium alloy powders with a Ti content of not less than 80% by mass, specifically:

[0052] A spherical titanium alloy powder containing alloy element Al content of 3.0%-7.0%, V content of 3.0%-5.0%, Mo content of ≤5.0%, Zr content of ≤5.0wt.%, the total mass fraction of other elements less than 0.5%, the mass fraction of impurity element S less than 0.01%, and Ti content of not less than 80%; the particle size of the spherical titanium alloy powder is in the range of 45μm-150μm and conforms to the spherical alloy powder of normal distribution.

[0053] The second type of laser cladding alloy raw materials are titanium alloy composite alloy powders composed of spherical titanium alloy powders with a Ti content of not less than 85% by mass and single Mo powder, specifically:

[0054] A titanium alloy composite alloy powder comprising a spherical titanium alloy powder having a particle size in the range of 45 μm to 150 μm and conforming to a normal distribution and uniformly mixed with a pure Mo powder, wherein the mass fraction of the alloy element Al content is 3.0% to 7.0%, the mass fraction of V content is 2.0% to 5.0%, the mass fraction of the total content of other elements is less than 0.5%, the mass fraction of the impurity element S content is less than 0.01%, the mass fraction of Ti content is not less than 85%; and the powder is a titanium alloy.

[0055] In the titanium alloy composite alloy powder, the mass proportion of spherical titanium alloy powder is 94.0%-97.0%;

[0056] In the titanium alloy composite alloy powder, the mass fraction of pure Mo powder is 3.0%-6.0%; the particle size of pure Mo powder is 10μm-55μm; the mass fraction of molybdenum content in pure Mo powder is not less than 99%.

[0057] Using the selected laser cladding alloy powder, a continuous wave fiber laser with a power of not less than 4kW, a turntable quantitative-pneumatic conveying powder feeder, a coaxial powder feeding laser head, and an ABB 6-axis robot, and nitrogen as the protective gas, laser cladding was carried out on ALPHA (α) titanium alloy, NEAR-ALPHA (near-α) titanium alloy and ALPHA-BETA (α-β) titanium alloy substrates that do not contain Sn, Pd, and Ru, and a laser cladding titanium alloy cladding layer with a hardness of more than 50HRC and good wear resistance was obtained.

[0058] Use a multimode continuous wave fiber laser with a power of not less than 4kW, a laser wavelength of 1070nm, and a coaxial powder feeding laser head for laser cladding; use positive defocus during laser cladding, and the spot diameter on the cladding surface is 3mm; use a turntable quantitative-pneumatic powder feeder to transport the laser cladding alloy raw materials, and use argon with a purity of more than 99.9% as the powder feeding gas. The distance from the intersection of the powder feeding powder to the cladding surface is 1±0.2mm; the nitrogen used for the shielding gas is high-purity nitrogen, with a nitrogen content of more than 99.99% and an oxygen content of less than 0.01%. The diameter of the laser head nozzle outlet is 8mm, and the shielding gas nitrogen flow rate is 29L / min-32L / min.

[0059] The specific steps are:

[0060] S1. Preparation of raw materials for laser cladding alloy:

[0061] Prepare laser cladding alloy raw materials according to the set requirements. For titanium alloy composite alloy powder as laser cladding alloy material, the mixed powder needs to be prepared according to the set ratio, and the prepared titanium alloy composite alloy powder is mixed evenly with a JHT20 double-motion powder mixer;

[0062] Titanium alloy powder or titanium alloy composite alloy powder, the raw material of laser cladding alloy, must be dried before use;

[0063] S2. Clean the surface of the workpiece where laser cladding is required:

[0064] Clean the surface of the part (base material) that needs laser cladding on the workpiece: remove oil, remove any surface contaminants, and grind the rough base surface until the surface roughness is lower than Ra6.3. When the room temperature is lower than 15°C, the base material needs to be preheated before cladding, and the preheating temperature is 150°C;

[0065] S3, Laser Cladding:

[0066] The laser cladding equipment uses a continuous wave fiber laser with a power of not less than 4kW, a turntable quantitative-pneumatic powder conveying feeder, a coaxial powder feeding laser head, a cooling water system, a pressure regulating and flow control and delivery device for the powder feeding gas argon, a pressure regulating and flow control device for the protective gas nitrogen, and an ABB 6-axis robot to form a linkage laser cladding system for laser cladding.

[0067] Among them, a turntable quantitative-pneumatic powder feeder is used to transport the laser cladding alloy raw materials, and argon with a purity higher than 99.9% is used as the powder feeding gas.

[0068] The nitrogen used as the protective gas is high-purity nitrogen with a nitrogen content higher than 99.99% and an oxygen content lower than 0.01%.

[0069] Adjust relevant parameters before cladding: adjust the distance between the laser head nozzle and the surface to be clad, adjust the defocus distance, and adjust the size and uniformity of the laser spot on the workpiece surface;

[0070] Set the powder feeding rate;

[0071] Set the powder feeding gas pressure-flow;

[0072] Set the shielding gas pressure-flow;

[0073] Set the laser scanning speed;

[0074] Set the laser power according to the required laser energy density;

[0075] Set the overlay width between laser cladding passes;

[0076] Operate the controller-robot for laser cladding;

[0077] S4. Post-processing of laser cladding:

[0078] The surface of the laser cladding layer is ground as required.

[0079] The invention is suitable for laser cladding on ALPHA (α) titanium alloy, NEAR-ALPHA (near-α) titanium alloy and ALPHA-BETA (α-β) titanium alloy substrates which do not contain Sn, Pd or Ru.

[0080] The wear-resistant alloy layer laser clad on the titanium alloy surface according to the present invention has the following characteristics:

[0081] (1) Metallographic observation shows that there is a dendritic dispersed hard phase in the laser cladding alloy layer using nitrogen as the protective gas.

[0082] (2) SEM-EDS observation and analysis combined with XRD analysis showed that the dendritic phase was titanium nitride.

[0083] (3) On a titanium alloy substrate with a hardness of 30±3HRC, the hardness of the alloy layer laser clad with nitrogen as the shielding gas is 53HRC-57HRC, which is significantly higher than that with argon as the shielding gas under the same process material.

[0084] (4) The wet sand-rubber wheel abrasive wear test results conducted according to ASTM G105 standard show that the wear amount of the cladding layer laser clad using nitrogen as the shielding gas according to the present invention is less than 1 / 2 of the wear amount of the cladding layer laser clad using argon as the shielding gas. Specific embodiment 1:

[0086] A spherical titanium alloy powder was used as the laser cladding alloy powder, and argon gas with a flow rate of 30L / min and nitrogen gas with a flow rate of 30L / min were used as the shielding gas, respectively, and laser cladding was performed according to the above laser cladding steps to prepare samples TA and TN. Then, the wet sand-rubber wheel abrasive wear test was performed on the samples TA and TN according to the ASTMG105 standard, the hardness of the cladding layer was tested with a HR-150A Rockwell hardness tester, the microstructure was observed with a DP-TOP optical metallographic microscope, and the microhardness was tested with a WS-ATM+CCD microhardness tester, and the changes in the performance of the laser cladding layer obtained by laser cladding of titanium alloy using nitrogen instead of argon as the shielding gas were investigated.

[0087] The specific operations are as follows:

[0088] Alloy powder for laser cladding: Spherical titanium alloy powder with the composition listed in Table 1 is used as alloy powder for laser cladding. The particle size of the powder is in the range of 45μm-100μm; Apparent Density: 2.49g / cm 3 .

[0089] Table 1

[0090]

[0091] Matrix material: Ti-6Al-4V-4Mo titanium alloy; size: length 90mm×width 40mm×thickness 15mm.

[0092] Laser cladding equipment-process parameters:

[0093] Use a 6 kW multimode continuous wave fiber laser, with a laser wavelength of 1070nm and a power of 3750W;

[0094] Use cohesive-reflective output-coaxial powder feeding laser head;

[0095] Light spot 3mm;

[0096] Use a rotary quantitative pneumatic powder feeder; use argon with a purity higher than 99.9% as the powder feeding gas, and the powder feeding gas flow rate is 25L / min;

[0097] Shielding gas: Argon or nitrogen is used as the shielding gas for laser cladding samples TA and TN:

[0098] Argon with a purity higher than 99.9% was used as the protective gas for laser cladding sample TA, and the protective gas argon flow rate was 30L / min;

[0099] High-purity nitrogen with a nitrogen content higher than 99.99% and an oxygen content lower than 0.01% was used as the protective gas for laser cladding sample TN, and the protective gas nitrogen flow rate was 30 L / min.

[0100] Laser cladding was performed along the length direction of the sample substrate with an overlap width of 1 mm. Samples TA and TN were laser clad on the TI-6Al-4V-4Mo titanium alloy substrate. Figure 1 The photos of laser cladding specimens TA and TN are given.

[0101] In order to investigate the effect of using nitrogen as the shielding gas for titanium alloy laser cladding instead of argon as the shielding gas for titanium alloy laser cladding on the performance of the laser cladding layer, the following performance tests were carried out:

[0102] (1) Wet sand-rubber wheel abrasive wear test was carried out according to ASTM G105 standard;

[0103] Wet sand-rubber wheel abrasive wear specimens that meet the requirements of ASTM G105 were made by cutting, machining and surface grinding on the laser cladding specimens. Wet sand-rubber wheel abrasive wear test was carried out according to ASTM G105 standard. The mass of the specimens before and after abrasive wear was measured with a precision balance with a sensitivity of 1 / 10,000 (measurement sensitivity of 0.0001g), and the mass loss was calculated. Figure 2 The morphology photos of the worn samples after the wet sand-rubber wheel abrasive wear test of sample TA and sample TN according to ASTM G105 standard are given. It can be seen that the depth of the wear groove of sample TA laser clad with argon as the shielding gas is significantly higher than the depth of the wear groove of sample TN laser clad with nitrogen as the shielding gas. Table 2 shows the test results of the wear loss of sample TA and sample TN in the wet sand-rubber wheel abrasive wear test according to ASTM G105 standard.

[0104] Table 2

[0105]

[0106] From the test results in Table 2, it can be seen that the wear amount of the laser cladding layer of the titanium alloy laser cladding with nitrogen as the protective gas is significantly lower than the wear amount of the laser cladding layer of the titanium alloy laser cladding with argon as the protective gas. This shows that using nitrogen as the protective gas instead of argon as the protective gas for titanium alloy laser cladding can significantly improve the wear resistance of the laser cladding layer.

[0107] (2) The hardness of the laser cladding layer was tested on the laser cladding specimens;

[0108] The hardness of the laser cladding layer of the laser cladding sample TA with argon as the shielding gas and the laser cladding sample TN with nitrogen as the shielding gas were tested using a HR-150A Rockwell hardness tester. The test results are listed in Table 3.

[0109] Table 3

[0110]

[0111] From the hardness test results, it can be seen that the hardness of the laser cladding layer of the titanium alloy cladding sample TN using nitrogen as the protective gas (56HRC±1HRC) is higher than the hardness of the laser cladding alloy layer of the cladding sample TA using argon as the protective gas (28HRC±1HRC). This shows that using nitrogen as the protective gas instead of argon as the protective gas for titanium alloy laser cladding can significantly improve the hardness of the laser cladding layer.

[0112] (3) The laser cladding samples were observed using an optical metallographic microscope;

[0113] Compare the metallographic photos of the cross section of the laser cladding layer of the laser cladding sample TA observed under an optical metallographic microscope magnified 200 times (see Appendix Figure 3 ) and metallographic photographs of the cross section of the laser cladding layer of the laser cladding sample TN observed under an optical metallographic microscope magnified 200 times (Attached Figure 5 ); see that the metallographic structures of the two are obviously different.

[0114] SEM-EDS observation and analysis combined with XRD phase analysis showed that titanium nitride was generated in the cladding layer using nitrogen as the protective gas.

[0115] (4) Microhardness test of laser cladding samples:

[0116] The microhardness of laser cladding samples TA and TN were tested using WS-ATM+CCD microhardness tester.

[0117] Figure 4 A microhardness test photograph of a titanium alloy laser cladding sample TA using argon as a protective gas in specific embodiment 1 is given; Figure 4 The hardness values ​​of each microhardness measurement point are listed in Table 4. Table 4 is a microhardness test photo corresponding to the laser cladding sample TA with argon as the protective gas. Figure 3 The hardness value of each microhardness measurement point (WS-ATM+CCD microhardness tester can display the corresponding HRC hardness value at the same time).

[0118] Table 4

[0119]

[0120] Figure 6 The microhardness test photos of the laser cladding sample TN using nitrogen as the protective gas in the specific embodiment 1 are given. The hardness values ​​of each microhardness measurement point in the figure are listed in Table 5. Table 5 is the microhardness test photos corresponding to the laser cladding sample TN using nitrogen as the protective gas Figure 6The hardness value of each microhardness measurement point (WS-ATM+CCD microhardness tester can display the corresponding HRC hardness value at the same time).

[0121] Table 5

[0122]

[0123] Comparing the microhardness measurement data listed in Table 4 and Table 5, we can see that the hardness of the laser cladding layer of the laser cladding sample TN with nitrogen as the protective gas (643.88HV, 617.77HV) is significantly higher than the hardness of the laser cladding layer of the laser cladding sample TA with argon as the protective gas (362.99HV, 345.11HV). This shows that using nitrogen as the protective gas instead of argon as the protective gas for titanium alloy laser cladding can significantly improve the microhardness of the laser cladding layer.

[0124] From the above test results, it can be seen that using nitrogen as the protective gas instead of argon as the protective gas for titanium alloy laser cladding can significantly improve the hardness and wear resistance of the titanium alloy laser cladding layer. Specific embodiment 2:

[0126] Specific Example 2 A titanium alloy composite alloy powder uniformly mixed with 96wt.% of spherical titanium alloy powder as listed in Table 1 and 4wt.% of pure Mo powder is used as laser cladding alloy powder, argon gas with a flow rate of 30L / min and nitrogen gas with a flow rate of 30L / min are used as protective gas, respectively, and laser cladding is performed according to the above laser cladding steps to prepare samples TMA and TMN. Then, the wet sand-rubber wheel abrasive wear test is performed on the samples TMA and TMN according to the ASTMG105 standard, the hardness of the cladding layer is tested with a HR-150A Rockwell hardness tester, the microstructure is observed with a DP-TOP optical metallographic microscope, and the microhardness is tested with a WS-ATM+CCD microhardness tester, and the change in the performance of the laser cladding layer obtained by laser cladding of titanium alloy with nitrogen instead of argon as protective gas is investigated.

[0127] The specific operations are as follows:

[0128] Alloy powder for laser cladding: composite alloy powder uniformly mixed with titanium alloy powder and single metal powder (hereinafter referred to as titanium alloy composite alloy powder). Specifically, the composite alloy powder uniformly mixed with 96% by mass of spherical titanium alloy powder and 4% by mass of pure Mo powder is used as alloy powder for laser cladding, wherein: the chemical composition of the 96% by mass of spherical titanium alloy powder is listed in Table 1, and the particle size of the powder is in the range of 45μm-100μm; Apparent Density: 2.49g / cm 3 .

[0129] The pure Mo powder with a mass ratio of 4% is a pure Mo powder with a Mo content of 99.8%, an oxygen content of less than 0.088%, and a particle size of 10μm-55μm. The mixed alloy powder prepared according to the mass ratio is mixed evenly in a JHT20 double-motion powder mixer for 24 hours and then used. It needs to be dried before use in laser cladding.

[0130] Matrix material: TI-6Al-4V-4Mo titanium alloy; size: length 90mm×width 40mm×thickness 15mm.

[0131] Laser cladding equipment-process parameters:

[0132] Use a 6 kW multimode continuous wave fiber laser, with a laser wavelength of 1070nm and a power of 3750W;

[0133] Use cohesive-reflective output-coaxial powder feeding laser head;

[0134] Spot diameter: 3mm;

[0135] Use a rotary quantitative pneumatic powder feeder; use argon with a purity higher than 99.9% as the powder feeding gas, and the powder feeding gas flow rate is 25L / min;

[0136] Shielding gas: Argon or nitrogen is used as the shielding gas for laser cladding samples TMA and TMN:

[0137] The argon gas with a purity higher than 99.9% was used as the protective gas for laser cladding sample TMA, and the protective gas argon gas flow rate was 30L / min;

[0138] High-purity nitrogen with a nitrogen content higher than 99.99% and an oxygen content lower than 0.01% was used as the shielding gas for the laser cladding sample TMN, and the shielding gas nitrogen flow rate was 30 L / min.

[0139] Laser cladding was carried out along the length direction of the sample substrate with an overlap width of 1 mm. Argon was used as the protective gas for laser cladding sample TMA, and nitrogen was used as the protective gas for laser cladding sample TMN on the TI-6Al-4V-4Mo titanium alloy substrate.

[0140] In order to investigate the effect of using nitrogen as the shielding gas for laser cladding of titanium alloy composite alloy powder instead of the commonly used argon as the shielding gas for laser cladding of titanium alloy composite alloy powder on the performance of the laser cladding layer, the following performance tests were carried out:

[0141] (1) Wet sand-rubber wheel abrasive wear test was carried out according to ASTM G105 standard;

[0142] Wet sand-rubber wheel abrasive wear specimens that meet the ASTMG105 standard were cut, machined, and surface ground on the laser cladding specimens. Wet sand-rubber wheel abrasive wear tests were conducted according to the ASTMG105 standard. The mass of the specimens before and after abrasive wear was measured with a precision balance of one ten-thousandth sensitivity (measurement sensitivity of 0.0001g), and the mass loss was calculated. Figure 7 The morphology photos of the worn samples after the wet sand-rubber wheel abrasive wear test of the sample TMA and the sample TMN according to the ASTMG105 standard are given. It can be seen that the depth of the wear groove of the sample TMA laser clad with argon as the shielding gas is significantly higher than the depth of the wear groove of the sample TMN laser clad with nitrogen as the shielding gas. Table 6 shows the test results of the wet sand-rubber wheel abrasive wear test of the sample TMA and the sample TMN according to the ASTMG105 standard.

[0143] Table 6

[0144]

[0145] From the test results in Table 6, it can be seen that the wear amount of the laser cladding layer of the sample TMN clad with titanium alloy composite alloy powder laser cladding using nitrogen as the shielding gas is significantly lower than the wear amount of the laser cladding layer of the sample TMA clad with titanium alloy composite alloy powder laser cladding using argon as the shielding gas. This shows that using nitrogen as the shielding gas instead of argon as the shielding gas for titanium alloy composite alloy powder laser cladding can significantly improve the wear resistance of the laser cladding layer.

[0146] (2) The hardness of the laser cladding layer was tested on the laser cladding specimens;

[0147] The hardness of the laser cladding layer of the laser cladding sample TMA which was laser clad with titanium alloy composite alloy powder using argon as the shielding gas and the laser cladding sample TMN which was laser clad with titanium alloy composite alloy powder using nitrogen as the shielding gas were tested using a HR-150A Rockwell hardness tester. The test results are listed in Table 7.

[0148] Table 7

[0149]

[0150] From the hardness test results, it can be seen that the hardness of the laser cladding layer of the titanium alloy composite alloy powder laser cladding sample TNN (55.5HRC±1HRC) using nitrogen as the protective gas is higher than the hardness of the laser cladding alloy layer of the titanium alloy composite alloy powder laser cladding sample TMA (39.5HRC±1.5HRC) using argon as the protective gas. This shows that using nitrogen as the protective gas instead of argon as the protective gas for titanium alloy composite alloy powder laser cladding can significantly improve the hardness of the laser cladding layer.

[0151] (3) The laser cladding samples were observed using an optical metallographic microscope;

[0152] Compare the metallographic photos of the cross section of the laser cladding layer of the laser cladding sample TMA observed under an optical metallographic microscope magnified 200 times (see Appendix Figure 8 ) and metallographic photographs of the cross section of the laser cladding layer of the laser cladding sample TMN observed under an optical metallographic microscope magnified 200 times (Attached Fig.10 The metallographic structure of the laser cladding layer of the sample TMN with nitrogen as the protective gas has obvious dendrite characteristics.

[0153] SEM-EDS observation and analysis combined with XRD phase analysis showed that titanium nitride was generated in the cladding layer using nitrogen as the protective gas.

[0154] (4) Microhardness test of laser cladding samples:

[0155] The microhardness of laser cladding samples TMA and TMN were tested using WS-ATM+CCD microhardness tester.

[0156] Fig. 9 The microhardness test photos of the titanium alloy composite alloy powder laser cladding sample TMA in the specific embodiment 1 are given with argon as the protective gas. The hardness values ​​of each microhardness measurement point in the figure are listed in Table 8. Table 8 is the microhardness test photos corresponding to the laser cladding sample TMA Fig. 9 The hardness value of each microhardness measurement point (WS-ATM+CCD microhardness tester can display the corresponding HRC hardness value at the same time).

[0157] Table 8

[0158]

[0159] Fig.11 The microhardness test photos of the laser cladding sample TMN using nitrogen as the protective gas in specific embodiment 2 are given. The hardness values ​​of each microhardness measurement point in the figure are listed in Table 9. Table 9 shows the microhardness test photos corresponding to the laser cladding sample TMN. Fig.11 The hardness value of each microhardness measurement point (WS-ATM+CCD microhardness tester can display the corresponding HRC hardness value at the same time).

[0160] Table 9

[0161]

[0162] Fig.12 The specific embodiment 2 in which nitrogen is used as the protective gas in the laser cladding sample TMN cladding layer is given. Fig.11 The microhardness test photos of the area. The hardness values ​​of each microhardness measurement point in the figure are listed in Table 10. Table 10 is the microhardness test photos corresponding to the laser cladding sample TMN Fig.12 The hardness value of each microhardness measurement point (WS-ATM+CCD microhardness tester can display the corresponding HRC hardness value at the same time).

[0163] Table 10

[0164]

[0165] Comparing the microhardness measurement data listed in Table 8, Table 9 and Table 10, it can be seen that the hardness of the laser cladding layer of the titanium alloy composite alloy cladding sample TMN laser cladding with nitrogen as the protective gas (615.67HV-6662.03HV) is significantly higher than the hardness of the laser cladding layer of the titanium alloy composite alloy sample TMA laser cladding with argon as the protective gas (374.52HV, 418.13HV). This shows that using nitrogen as the protective gas instead of argon as the protective gas for titanium alloy laser cladding can significantly improve the microhardness of the laser cladding layer.

[0166] From the test results of the above embodiments, it can be seen that using nitrogen as the protective gas instead of argon as the protective gas for laser cladding of titanium alloy composite alloys can significantly improve the hardness and wear resistance of the titanium alloy laser cladding layer.

[0167] Attached Fig.13 The micro-area SEM-EDS analysis photos of the dendrite structure of the TMN laser cladding layer of the titanium alloy composite alloy powder laser cladding sample with nitrogen as the protective gas in the specific embodiment 2 of the present invention are given. From the micro-area SEM-EDS component analysis results of the dendrite structure of the TMN laser cladding layer, it can be seen that the dendrite structure of the TMN laser cladding layer of the titanium alloy composite alloy powder laser cladding sample with nitrogen as the protective gas contains 66.04at.% of titanium and 27.21at.% of nitrogen. Combined with XRD analysis, it is shown that titanium nitride (Ti2N) phase is generated. It is noted that aluminum (3.56at.%), vanadium (1.71at.%) and molybdenum (1.47at.%) are dissolved in the titanium nitride phase at the same time. (The issue of using nitrogen as a shielding gas to laser clad titanium alloy to obtain an in-situ endogenous titanium nitride hard phase is not the focus of this application. The focus of this application is to use nitrogen as a shielding gas instead of argon as a shielding gas to laser clad titanium alloy, which can improve the hardness and wear resistance of the laser cladding layer).

[0168] The test results of the above specific embodiments 1 and 2 show that using nitrogen instead of the commonly used argon as the shielding gas and laser cladding titanium alloy can significantly improve the hardness and abrasive wear resistance of the laser cladding layer. The hardness of the laser cladding alloy layer using nitrogen as the shielding gas is above 50HRC, and the abrasive wear loss is less than 1 / 2 of the loss of the laser cladding alloy layer using argon as the shielding gas, and the relative wear resistance is improved by more than 2 times.

[0169] The present invention is described above by way of example in conjunction with the accompanying drawings. It is obvious that the specific implementation of the present invention is not limited to the above-mentioned method. As long as various improvements are made using the method concept and technical solution of the present invention, or are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.

Claims

1. A process for improving the wear resistance of laser cladding titanium alloy coating using nitrogen as protective gas, characterized in that: Titanium alloy powder or titanium alloy composite alloy powder without any hard particles is used as the raw material for laser cladding alloy. By adjusting the laser cladding equipment, laser parameters, and process parameters of powder feeding gas, and using nitrogen as the protective gas, laser cladding is carried out on ALPHA titanium alloy, NEAR-ALPHA titanium alloy, and ALPHA-BETA titanium alloy substrates that do not contain Sn, Pd, or Ru to obtain a laser cladding titanium alloy cladding layer.

2. The process for improving the wear resistance of laser cladding titanium alloy coating by using nitrogen as protective gas according to claim 1 is characterized in that: The raw material of laser cladding alloy is titanium alloy powder with a Ti content of not less than 80wet.%, specifically: A spherical titanium alloy powder containing alloy elements Al: 3.0wt.%-7.0wt.%, V: 3.0wt.%-5.0wt.%, Mo: ≤5.0wt.%, Zr ≤5.0wt.%, the total amount of other elements less than 0.5wt.%, the content of impurity element S less than 0.01 wt.%, and Ti content not less than 80wt.%; the particle size of the spherical titanium alloy powder is in the range of 45μm-150μm and conforms to the spherical alloy powder of normal distribution.

3. The process for improving the wear resistance of laser cladding titanium alloy coating by using nitrogen as protective gas according to claim 1 is characterized in that: The raw materials of laser cladding alloy are titanium alloy composite alloy powder composed of spherical titanium alloy powder with Ti content not less than 85wet.% and single Mo powder, specifically: A titanium alloy composite alloy powder containing alloy elements Al: 3.0wt.%-7.0wt.%, V: 2.0wt.%-5.0wt.%, the total amount of other elements less than 0.5wt.%, the content of impurity element S less than 0.01wt.%, the content of Ti not less than 85wt.%, and a spherical titanium alloy powder with a particle size in the range of 45μm-150μm that conforms to normal distribution and a pure Mo powder uniformly mixed; The amount of pure Mo powder added is in the range of 3wt.%-6wt.%; the particle size of the pure Mo powder is 10μm-55μm; and the molybdenum content of the pure Mo powder is not less than 99wt%.

4. The process for improving the wear resistance of laser cladding titanium alloy coating by using nitrogen as protective gas according to any one of claims 1 to 3, characterized in that: The specific steps are: S1. Preparation of raw materials for laser cladding alloy: Prepare laser cladding alloy raw materials according to the set requirements. For composite titanium alloy powder and composite alloy powder, the powders need to be mixed according to the set ratio and mixed evenly with a powder mixer. The laser cladding alloy raw materials should be dried before use; S2. Clean the surface of the workpiece where laser cladding is required: Degreasing and removing surface pollutants, the surface roughness of the substrate to be clad should be lower than Ra12.

6. When the room temperature is lower than 15°C, the substrate needs to be preheated before cladding, and the preheating temperature is 150°C; S3, Laser Cladding: Adjust relevant parameters before cladding: adjust the distance between the laser head nozzle and the surface to be clad, and adjust the size and uniformity of the laser spot on the workpiece surface; Set the powder feeding rate; Set the powder feeding gas pressure-flow; Set the shielding gas pressure-flow; Set the laser scanning speed; Set the laser power according to the required laser energy density; Set the overlap width between laser cladding passes; Operate the controller-robot for laser cladding; S4. Post-processing of laser cladding: The surface of the laser cladding layer is ground as required.

5. The process for improving the wear resistance of laser cladding titanium alloy coating by using nitrogen as protective gas according to claim 4 is characterized in that: Laser cladding is performed using a multi-mode continuous wave fiber laser with a power of not less than 4kW and a coaxial powder feeding laser head.

6. The process for improving the wear resistance of laser cladding titanium alloy coating by using nitrogen as protective gas according to claim 4 is characterized in that: A rotary quantitative pneumatic powder feeder is used to transport the laser cladding alloy raw materials, and argon with a purity higher than 99.9% is used as the powder feeding gas.

7. The process for improving the wear resistance of laser cladding titanium alloy coating by using nitrogen as protective gas according to claim 4 is characterized in that: The nitrogen used as the protective gas is high-purity nitrogen with a nitrogen content higher than 99.99% and an oxygen content lower than 0.01%.

Citation Information

Patent Citations

  • Airfoil and method of a repair the same

    CA2735299A1

  • Method for low-laser-power preparation of TiN gradient coating on titanium alloy surface

    CN107475662A

  • Preparation method of TiAlN coating on surface of titanium alloy

    CN111945152A

  • Method for preparing ceramic-reinforced laser-cladding refractory high-entropy alloy coating on surface of titanium alloy and application

    CN112962095A

  • Method for preparing wear-resistant coating on surface of titanium alloy through laser melt injection

    CN113463086A